Multi-Level Technological Advancements in Stability and Energy Efficiency of Railway Traction Power Supply Systems - Mingli Wu; Shaobing Yang; Kejian Song; Mengtong Li; Chi Ma (Energies, 2025)
Under the twin forces of global energy transition and transportation electrification in the 21st century, the railway system, as an efficient backbone transportation mode, has witnessed the optimization of power supply technology and energy efficiency emerging as a central challenge driving industrial innovation [...]